Features of functioning and legal regulation of the labor market in the Republic of Tuva under conditions of the COVID-19 pandemic and digital transformation - Popova, Popova S.; Yanik, Andrey A.; Kashepov, Alexey V. (The New Research of Tuva, 2023)
The article presents an analysis of the impact of extraneous shocks (the pandemic and digitalization) on the conditions of the labor market in the Republic of Tuva and prospects for increasing its adaptability to the challenges of a changing economy. The Republic has a complex economic structure and an unbalanced labor market. Along with the general underemployment and lack of employment opportunities for promising young people, there is a backlog demand for specialists who have the qualifications necessary for the Tuvan economy. The problem lies in the unresponsiveness of the Tuvan labor market to attempts to reverse negative trends. This complicates the transition of the Republic’s economy to an innovative development model. We have analyzed new phenomena in the Tuvan labor market that are related to the pandemic and digital transformation processes. The authors have considered opportunities for improving regulatory measures aimed at coping with the imbalances of the republican labor market, primarily the structural lack of labor resources. The impact of the pandemic is defined as ambivalent: amid economic difficulties and social losses, the external shock has become one of the incentives to accelerate the digital transformation in various spheres of life and activity, including the systems of education, employment and the economy as a whole. An attempt is made to assess the impact of new factors that emerged in 2022 (the introduction of international sanctions and partial mobilization) on the Tuvan labor market and its regulation.